2014
DOI: 10.1111/cogs.12156
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Phonological and Semantic Representations: Time Matters

Abstract: Computational modeling and eye-tracking were used to investigate how phonological and semantic information interact to influence the time course of spoken word recognition. We extended our recent models (Chen & Mirman, 2012; Mirman, Britt, & Chen, 2013) to account for new evidence that competition among phonological neighbors influences activation of semantically related concepts during spoken word recognition (Apfelbaum, Blumstein, & McMurray, 2011). The model made a novel prediction: Semantic input modulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…This also means that target object fixations can increase without an arithmetically equivalent decrease in distractor object fixation, particularly early in the time course when participants are likely to be looking at screen center until they have information that drives target fixation. The overall target fixation trajectory was modeled with a cubic polynomial as in previous studies (e.g., Chen & Mirman, 2015; Magnuson, Dixon, Tanenhaus, & Aslin, 2007). The hypotheses regarding anticipation were tested by adding effects of Condition (Restrictive vs. Non-Restrictive) and Group (Anterior vs. Posterior) on the intercept term, which captures the mean fixation proportion during the analysis time window (analogous to a repeated measures ANOVA), and on the linear term, which captures the linear increase in fixation proportions during the analysis time window.…”
Section: Resultsmentioning
confidence: 99%
“…This also means that target object fixations can increase without an arithmetically equivalent decrease in distractor object fixation, particularly early in the time course when participants are likely to be looking at screen center until they have information that drives target fixation. The overall target fixation trajectory was modeled with a cubic polynomial as in previous studies (e.g., Chen & Mirman, 2015; Magnuson, Dixon, Tanenhaus, & Aslin, 2007). The hypotheses regarding anticipation were tested by adding effects of Condition (Restrictive vs. Non-Restrictive) and Group (Anterior vs. Posterior) on the intercept term, which captures the mean fixation proportion during the analysis time window (analogous to a repeated measures ANOVA), and on the linear term, which captures the linear increase in fixation proportions during the analysis time window.…”
Section: Resultsmentioning
confidence: 99%
“…Chen & Mirman (2012) argue, on the basis of simulations in a domain-general interaction and competition model, that the reported pattern of facilitation and inhibition is predicted in any model in which multiple representations are activated in parallel: Weak competition (such as that posed by phonological neighbors in spoken word production) yields a net benefit for the target, whereas strong competition (such as that posed by phonological neighbors in spoken word recognition) results in target inhibition. More recently, Chen & Mirman (2015) have shown that phonological neighbors produce a facilitative effect even in spoken word recognition, when semantic context weakens the activation of phonological neighbors.…”
Section: Background: Phonological Neighborhood Density In Recognitionmentioning
confidence: 99%
“…Importantly, the category/domain-level similarity between concepts (both robin and stork different from tent) only emerged later, in the looks post-word offset. It is important to note that our assumption here is that the dynamics of semantic activation during the 3 s delay between display onset and word onset is constant across conditions (e.g., Chen & Mirman, 2015), and that any changes in that dynamic as a function of word type, as evidenced by the eye movement measure, will reflect the interaction between the prior semantic activation driven by the visual image, and the semantic dynamics associated with recognition of the unfolding word in the context of the visual scene. We return to the implications of these findings in the General Discussion.…”
Section: Discussionmentioning
confidence: 99%